Den barokke lov i Kafkas Processen - Simonsen, Karen-Margrethe (Passage - Tidsskrift for litteratur og kritik, 2011)
Karen-Margrethe Simonsen: “The Baroque Law in Kafka’s The Trial. Power and Labyrinth” This article argues that a baroque perspective on Kafka’s works and especially The Trial can help elucidate the relation between the power of law and its labyrinthine character. Most modern and postmodern studies of the neobaroque in the 20th Century focus only on the labyrinthine playfulness of the baroque and disregard the baroque’s interest in absolutistic power. In the article, it is shown how Kafka unites the two sides of the baroque. The article argues that there is absolute distance, yet concrete simultaneity between the worldly and the transcendent aspects of law in Kafka, and elaborates this by drawing in some aspects of Gilles Deleuze’s and Jacques Derrida’s readings of Kafka regarding this relation. Finally it discusses the modernity of Kafka through a very short detour around Tzvetan Todorov’s study of the fantastic.